An ethnographic investigation into the development and trialing of more accessible text materials for second language teaching and learning in physical science - Clark, Jonathan; Clark, Jonathan (School of Education, 2017)
This dissertation discusses the development of alternative science curriculum materials for a secondary schooling context where English, the medium of instruction, is a second language for both teachers and students. The research is located in an interpretative ethnographic framework and the data gathered during the classroom-based trialing of the materials highlights the vital role of language in the teaching and learning of school science. An interactive reading model coupled with a discourse approach to text analysis explores some of the language difficulties which black students experience with their science textbooks. That many students fail to develop adequate reading strategies is identified as lying at the heart of many learning problems. It is suggested that the key to comprehension is instruction from a base of more accessible text materials. Furthermore, although science practical work does not automatically advance students' knowledge and understanding, relevant and contextualised learning activities do equip students to become more self-directed and reflective learners of science.